2016
DOI: 10.1053/j.gastro.2016.01.032
|View full text |Cite
|
Sign up to set email alerts
|

The MBOAT7-TMC4 Variant rs641738 Increases Risk of Nonalcoholic Fatty Liver Disease in Individuals of European Descent

Abstract: Background & Aims Nonalcoholic fatty liver disease (NAFLD) is a leading cause of liver damage and is characterized by steatosis. Genetic factors increase risk for progressive NAFLD. A genome-wide association study showed that the rs641738 C>T variant in the locus that contains the membrane bound O-acyltransferase domain-containing 7 gene (MBOAT7, also called LPIAT1) and transmembrane channel-like 4 gene (TMC4) increased the risk for cirrhosis in alcohol abusers. We investigated whether the MBOAT7/TMC4 is a sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
605
7
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 560 publications
(700 citation statements)
references
References 48 publications
39
605
7
8
Order By: Relevance
“…Interestingly, the previous in silico analyses have also suggested that MBOAT7 could trigger arachidonic acid release and thus promote HCC-linked phenotypes, such as inflammation and fibrogenesis [45,98]. This hypothesis is in line with recent studies reporting higher levels of proinflammatory metabolites of arachidonic acid in patients with NASH [99], just as was observed in the association between a variant in MBOAT7 and increased risk of liver damage in ALD/NAFLD patients [30,100]. Overall, these observations highlight that PNPLA3, and more generally lipid turnover, may impact liver carcinogenesis.…”
Section: Hypothetical Mechanisms For Liver Cancer Promotionsupporting
confidence: 75%
“…Interestingly, the previous in silico analyses have also suggested that MBOAT7 could trigger arachidonic acid release and thus promote HCC-linked phenotypes, such as inflammation and fibrogenesis [45,98]. This hypothesis is in line with recent studies reporting higher levels of proinflammatory metabolites of arachidonic acid in patients with NASH [99], just as was observed in the association between a variant in MBOAT7 and increased risk of liver damage in ALD/NAFLD patients [30,100]. Overall, these observations highlight that PNPLA3, and more generally lipid turnover, may impact liver carcinogenesis.…”
Section: Hypothetical Mechanisms For Liver Cancer Promotionsupporting
confidence: 75%
“…The liver biopsy cohort (LBC) has been described 5, 15. A total of 1,388 adult individuals of European descent were consecutively enrolled from the Metabolic Liver Diseases outpatient service and bariatric surgery center, Fondazione IRCCS Ca' Granda Ospedale Policlinico Milano, Milan, Italy, and from the Northern Savo Hospital District, Kuopio, Finland.…”
Section: Methodsmentioning
confidence: 99%
“…The LBC cohort was genotyped for the rs738409 C>G ( PNPLA3 I148M), rs58542926 C>T (TM6SF2 E167K), rs1260326 C>T ( GCKR P446L), rs641738 C>T MBOAT7 , and rs4841132 G>A ( LOC157273‐PPP1R3B ) variants as described 5, 15. Genotyping of the LBC was performed in duplicate using TaqMan 5′‐nuclease assays (Life Technologies, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PNPLA3 is presented as minor allele frequency (that is, the fre quency at which the second most common PNPLA3 allele occurs in a population). Among the emerging newly discovered risk loci, variants near the genes encoding for membrane bound O acyltransferase domain containing 7 (MBOAT7) and transmembrane channel like 4 (TMC4) have been shown to be associated with development and severity of NAFLD in patients of European descent 101 . Similarly, within the Latino popu lation in South America, the TM6SF2 Glu167Lys and PNPLA3 Ile148Met protein variants seem to confer susceptibility to progressive NASH 102 .…”
Section: Risk Factors: Nature or Nurture?mentioning
confidence: 99%